Toward Testing for Multimodal Perception of Mating Signals - Halfwerk, Wouter; Varkevisser, Judith; Simon, Ralph; Mendoza, Ezequiel; Scharff, Constance; Riebel, Katharina (Frontiers in Ecology and Evolution, 2019)
Many mating signals consist of multimodal components that need decoding by several sensory modalities on the receiver’s side. For methodological and conceptual reasons, the communicative functions of these signals are often investigated only one at a time. Likewise, variation of single signal traits are frequently correlated by researchers with senders’ quality or receivers’ behavioural responses. Consequently, the two classic and still dominating hypotheses regarding the communicative meaning of multimodal mating signals postulate that different components either serve as back-up messages or provide multiple meanings. Here we discuss how this conceptual dichotomy might have hampered a more integrative, perception encompassing understanding of multimodal communication: neither the multiple message nor the back-up signal hypotheses address the possibility that multimodal signals are integrated neurally into one percept. Therefore when studying multimodal mating signals, we should be aware that multimodal signals can give rise to multimodal percepts, meaning that receivers can gain access to additional information inherent to only combined signal components (‘the whole is something different than the sum of its parts’). We review the evidence for the importance of multimodal percepts and outline potential avenues for discovery of multimodal percepts in animal communication.